Delayed repair for complex genital trauma following sexual assault in a 3-year-old female with late presentation for care: a case report - Raha Maroyi; Denis Mukwege; Lisa Doble; Robert Andrianne (Journal of Medical Case Reports)
Abstract Background Genital trauma following child sexual abuse presents a complex and variable clinical picture of pelvic perineal injury, necessitating a comprehensive understanding of the structures involved in effective management. Ideally, these cases are considered urgent, and primary repair should be performed as an emergency. Unfortunately, the window of opportunity for urgent action may be missed as the patient may not present for care until much later. Case presentation We report the case of a 3-year-old African (Congolese) girl who presented to the Panzi Hospital’s sexual violence ward in Bukavu, Democratic Republic of the Congo (DRC), 3 days after being sexually abused by an adult family friend. Clinical examination revealed a complex perineal tear with a split in the posterior vaginal wall extending to the posterior vaginal cul-de-sac and a fourth-degree rectal prolapse. A cleft was also noted in the external orifice of the urethral meatus. All the lesions were infected and covered with fibrin, with no signs of peritonitis. Initial management included admission for locoregional treatment with antiseptic solution and sitz baths. A total of 2 weeks later, surgical intervention was performed, which resulted in improved short- and long-term outcomes in terms of the vulvar cosmetic, functional, and psychological aspects. Conclusion In cases of delayed access to medical care for several days for complex genital trauma following child sexual abuse, treatment of the infection and delayed closure lead to better outcomes.